Balancing cost-efficiency and sustainability in offshore hybrid renewable energy systems: A case study of Palau River - Terkes, Musa; Syarif, Muhammad Rizqi Asy; Demirci, Alpaslan; Ozturk, Zafer; Gokalp, Erdin; Cali, Umit (ELSEVIER, 2025)
Increasing environmental concerns and regulations on carbon emissions necessitate the development of economically viable and sustainable renewable energy systems. In this context, comprehensively evaluating solar PV-based hybrid energy systems under carbon tax (CT) scenarios is critically important. This study comparatively analyzes the cost-effectiveness, sustainability, and economic impacts of carbon taxation on both grid-connected and off-grid system configurations. Specifically, the effects of a CT on the costs of grid-connected system architectures are examined in detail, and cost reduction rates at various CTs are presented. By comparing different configurations in terms of technical performance and environmental benefits, optimal sizing strategies are determined to balance cost and carbon emissions. The results indicate that CT implementation provides a cost advantage in grid-connected systems, leading to a reduction in total system costs by approximately 15-22 %. Moreover, hybrid systems demonstrate significant improvements in environmental sustainability. These findings clearly highlight a critical role of CT policies in renewable energy integration and the economic and environmental benefits of hybrid energy systems.
Keywords: Carbon neutrality; Carbon tax; Floating solar; Offshore wind turbine; Optimization; Tidal/wave energy; WIND; TECHNOLOGY; SOLAR; LOSSES; RISKS; MODEL; Energy & Fuels